"Unsere eigene Vernunfft hat die Complimenten erdacht" – The Romantic Novel between Discourses of Behaviour and Language (KULT_online, 2009)
German scholar Florian Gelzer turns his attention to a largely unstudied tradition in German literature in his dissertation Konversation, Galanterie und Abenteuer (2007). Gelzer reconstructs complex interactions between Romanesque literature, the French discourse on behaviour, German Enlightenment philosophy and chivalric reflections on language from the late 17th and the 18th century in Germany. Between the baroque and early enlightenment periods, in conjunction with international discourses and literary forms shaped by intertextuality, the genre of romantic novel arose – a category that Gelzer defines as neither a "vestige" of earlier texts nor a precursor to later forms. In so doing, Gelzer makes a decisive contribution to the clarification and reappraisal of early modern literature.